The rationale for the current boom in anti-TNFα treatment. Is there an effective means to define therapeutic targets for drugs that provide all the benefits of anti-TNFα and minimise hazards?. (1st November 1999) - Feldmann, Marc; Bondeson, Jan; Brennan, Fionula M; Foxwell, Brian M J; Maini, Ravinder N
Abstract : Progress in understanding mechanisms of disease are necessary to usher in major changes in treatment. A new era in rheumatoid arthritis (RA) and related chronic autoimmune/inflammatory diseases is now beginning, with a variety of anti-TNFα treatments licensed for use in both RA and Crohn's disease. The rationale for this new treatment lies in an understanding that cytokines are critical, rate limiting molecules lying at the heart of the chronic autoimmune/inflammatory disease process. This understanding was developed from the critical evaluation of a hypothesis that was proposed linking cytokines, antigen presentation and autoimmunity in 1983. Detailed analysis focusing on the major site of the disease, the rheumatoid synovium was essential to developing indications that blockade of TNFα might be efficacious. This clue was validated using anti-TNFα treatment of an animal model of RA, murine collagen induced arthritis, and by immunohistochemical demonstration of upregulated TNF and TNF-R expression in the synovium. With this three pronged rationale, the authors were able to convince Centocor, Inc, which had developed a chimaeric anti-TNFα antibody for use in sepsis, to work with them to test the concept that TNFα blockade would be beneficial in RA. With the success of that first trial, other companies have subsequently tested their anti-TNF strategies successfully. Current interests extend to understanding the processes that regulate TNF production in the rheumatoid joint. Progress in this area is discussed, using adenoviruses to infect normal macrophages and rheumatoid synovium.